(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the clinical and pathogenetic characteristics of acute and chronic hepatosis, differences in treatment strategies, and modern therapeutic approaches. It highlights the necessity for emergency medical intervention in acute cases and outlines the importance of long-term, complex therapy, diet, and lifestyle changes in chronic hepatosis. The article presents data on the use of hepatoprotectors, antioxidants, insulin sensitizers, and antifibrotic medications, emphasizing the effectiveness of individualized treatment strategies based on etiology.